“Proyecto de factibilidad de una micro empresa productora de galletas energéticas (Guayusa)” - Sandoval Cantuña, Josehp Dario (2021)
The main objective of this research is to present a feasibility study, through a business plan to create a micro-business about energy cookies based on the guayusa plant. Therefore, to collect information, the inductive and analytical method was applied through the survey technique to a representative sample of the population in Quito's Historic center, where the company will be developed. So, to demonstrate the feasibility of this business, it is necessary to indicate that different studies are developed such as, the business market one which allows an orientation to the specific segment. The technical study, which shows the essential aspects for the operation, and the financial one, demonstrates the economic feasibility of the business. For this reason, this business is so important because it aims to mark a competitive advantage and be a quality product that benefits the population.